EKSISTENSI KESENIAN TUNDANG MAYANG SANGGAR PUSAKA DESA SUNGAI BURUNG KABUPATEN MEMPAWAH - Sari, Purmini Mayang; Djau, Nurmila Sari; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractExistence of Tundang Mayang art of sanggar Pusaka Sungai Burung village Mempawah Districts, This reseacrch is motivated by the desire of researcers to find out the existence of Tundang Mayang art of sanggar Pusaka desa Sungai Burung Kabupaten Mempawah. The purpose of this study is: 1). Describe the existence of Tundang Mayang art sanggar Pusaka Sungai Burung village Mempawah districts 2). Describe the factors thet influence the existence of Tundang Mayang art sanggar Pusaka Sungai Burung village Mempawah Districts 3). Describe the Implementation of Tundang Mayang sanggar Pusaka on learning art and culture at school. Research data consist of the existence of Tundang Mayang sanggar Pusaka, factors that influence the existence of Tundang art and efforts to maintain the existence of Tundang Mayang art. Data collection techniques such as observation, interview and documantation. The technique of checking the validity of the data consist of, of extension,of obsevation dan triangulation technique. The analysis technique used is to analyze the data of research results regarding the existence of Tundang Mayang and then consult the resulats of research with the main supervisor and the scond supervisor and conclude the results of the study about the existence of Tundang Mayang art of sanggar Pusaka village Sungai Burung Mempawah Districts .The results of the study are :1) The existence of Tundang Mayang art began the existennce of Tundang Mayang art began in 1992 until now.2) Factors that influence the existence of Tundang Mayang art are the needs of society,culture, economic factors, lack of interest and knowledge. 3) Efforts made by the community and the group of Tundang Mayang. 4) design of the results with a valid currculum as teaching material for arts and culture and skills( Music art) in schools. Keywords : Existence, Tundang Mayang, Sanggar Pusaka.